Inclusion, one more chromosome (Down Syndrome) in education (Research, Society and Development, 2021)
This article aims to investigate the inclusion of the student with an extra chromosome in this case the so-called Down Syndrome in education. Currently, there is a lot of talk about Inclusive Education, and within this school modality, one of the subjects that one is interested in understanding is the concepts of Down Syndrome. DS is not a disease, but a condition, an irregular condition to the person, a genetic alteration, which makes normal development impossible like other healthy individuals. However, it involves health issues, from birth to the child and must be accompanied by qualified professionals. Each person reacts in their own time in a different way to the treatment, according to their genetics, their way of interacting, their evolution will occur according to their needs. It can be said that people with DS are more alike than they are different. Without a doubt, the school is considered an ideal environment for building and transmitting knowledge such as culture and shaping citizens, however, to receive a SD child, it is essential that the school has more qualified professionals and teaching materials for education Special. Thus, the main purpose of this research is the development of students with an extra chromosome in school life. We have our Federal Constitution which ensures that all citizens, without exception, of beliefs, color, race, have the right to education, including people with disabilities, in this case Down Syndrome, it is observed that even if included in regular education , well received, it cannot be said that their needs are satisfactory, as there may be a lack of physical structure in schools, such as: accessibility and unprepared teachers. As well as the lack of a multidisciplinary team that counts with: Psychologists, Psychiatrists, Occupational Therapists, Physiotherapists, Psychopedagogists and Speech-Language Pathologists, who must monitor the students with DS. This work is very important so that people with DS should be included in society, not because of a law, but because they are human, and within their conditions they share, affection, love, learn and interact with people called "normal". It is worth emphasizing the need to alert families, educators and society about the characteristics of DS patients, demonstrating how they can deal with and eliminate prejudice and make them aware that they are capable and productive.